Web Based Midwife Reservation System with Laravel PHP and MySQL Database - Lioner, Teddy; Febryatna, Rinaldi; Sudewo, Andika Hasbigumdi; Maolani, Yusup; Widyarto, Setyawan (Proceedings of the Informatics Conference, 2025)
In recent years, web applications have increasingly streamlined administrative processes in various domains; however, specialized solutions for midwives remain limited. This study addresses this gap by developing a web-based midwife reservation system using the Laravel PHP framework and MySQL database. The system is designed to support efficient scheduling, enhance patient engagement, and provide open-source accessibility to promote collaboration and customization. Key features include automated appointment management, timely notifications, and user-friendly interfaces tailored to the unique requirements of midwives and patients. The development process adopts agile and kanban methodologies to ensure flexibility, iterative improvements, and alignment with user needs, while black-box testing is employed to validate functionality and reliability. The proposed system demonstrates the potential of web-based technologies to improve healthcare services for midwives, optimize administrative efficiency, and strengthen patient-provider interactions.